Surface electrical stimulation of the quadriceps femoris in patients affected by haemophilia A - QUEROL, F.; GALLACH, J. E.; TOCA-HERRERA, J. L.; GOMIS, M.; GONZALEZ, L-M. (Haemophilia : the official journal of the World Federation of Hemophilia, 2006)
Eighteen sessions of surface electrical stimulation was applied to the quadriceps femoris of the left leg of ten male subjects affected by severe haemophilia A, while ten healthy subjects constituted the control group. The isometric strength, the electromyographic activity and the diameter of the rectus femoris were measured in both legs before and after a six‐week treatment period. After the treatment, the people affected by haemophilia showed a gain in strength by 13.8% in the stimulated leg and by 17.1% in the non‐stimulated one. No changes were detected in the electromyographic activity. On the contrary, the diameter of the rectus femoris of the stimulated leg increased in 24.34%, while no significant change was found in the nonelectrically stimulated leg. These results show for the first time that the application of electrical stimulation in haemophilic patients contributes to the gain and development of strength and trophism. The results also show that the surface electrical stimulation does not represent a threat to the patients' health, and that can be used for therapeutic purposes.